Iron alters macrophage polarization status and leads to steatohepatitis and fibrogenesis. Issue 5 (5th March 2019) - Handa, Priya; Thomas, Sunil; Morgan‐Stevenson, Vicki; Maliken, Bryan D.; Gochanour, Eric; Boukhar, Sarag; Yeh, Matthew M.; Kowdley, Kris V.
Abstract: We have previously demonstrated that iron overload in hepatic reticuloendothelial system cells (RES) is associated with severe nonalcoholic steatohepatitis (NASH) and advanced fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). Recruited myeloid‐derived macrophages have gained a pivotal position as drivers of NASH progression and fibrosis. In this study, we used bone marrow‐derived macrophages (BMDM) from C57Bl6 mice as surrogates for recruited macrophages and examined the effect of iron on macrophage polarization. Treatment with iron (ferric ammonium citrate, FAC) led to increased expression levels of M1 markers: CCL2, CD14, iNOS, IL‐1β, IL‐6, and TNF‐α; it also increased protein levels of CD68, TNF‐α, IL‐1β, and IL‐6 by flow cytometry. This effect could be reversed by desferrioxamine, an iron chelator. Furthermore, iron loading of macrophages in the presence of IL‐4 led to the down‐regulation of M2 markers: arginase‐1, Mgl‐1, and M2‐specific transcriptional regulator, KLF4. Iron loading of macrophages with IL‐4 also resulted in reduced phosphorylation of STAT6, another transcriptional regulator of M2 activation. Dietary iron overload of C57Bl6 mice led to hepatic macrophage M1 activation. Iron overload also stimulated hepatic fibrogenesis. Histologic analysis revealed that iron overload resulted in steatohepatitis. Furthermore, NAFLD patients with hepatic RES iron deposition had increased hepatic gene expression levels of M1 markers, IL‐6, IL‐1β, and CD40 and reduced gene expression of an M2 marker, TGM2, relative to patients with hepatocellular iron deposition pattern. We conclude that iron disrupts the balance between M1/M2 macrophage polarization and leads to macrophage‐driven inflammation and fibrogenesis in NAFLD. Abstract : Iron‐mediated impairment of macrophage polarization contributes to exacerbation of hepatic inflammation and nonalcoholic fatty liver disease.